2005
DOI: 10.1021/bi051336u
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Modification of Proteasome:  Identification of an Oxidation-Sensitive Subunit in 26 S Proteasome

Abstract: Reactive oxygen species (ROS) have the potential to damage cellular components, such as protein, resulting in loss of function and structural alteration of proteins. The oxidative process affects a variety of side amino acid groups, some of which are converted to carbonyl compounds. We have previously shown that a prostaglandin D2 metabolite, 15-deoxy-delta(12,14)-prostaglandin J2 (15d-PGJ2), is the potent inducer of intracellular oxidative stress on human neuroblastoma SH-SY5Y cells [Kondo, M., Oya-Ito, T., K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
111
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 29 publications
10
111
1
1
Order By: Relevance
“…Additionally, oxidation of Rpn1 and Rpn2 did not affect their association with the 20 S CP. However, in contrast to our study, diminished 26 S proteolytic activity has been found to be accompanied by a loss of 26 S proteasomal structure following exposure to metal-catalyzed oxidation as a result of carbonylation involving one of the S6 ATPase regulatory subunits (58). Strong oxidation of the 26 S proteasome under non-physiologic conditions can occur by exposure to hydroxyl radical generated in metal catalyzed reactions; in the present study, exposure of the 26 S proteasome to GSH and H 2 O 2 was performed in the presence of metal chelator diethylenetriaminepentaacetic acid, eliminating the possibility of such hydroxyl radical-associated events.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, oxidation of Rpn1 and Rpn2 did not affect their association with the 20 S CP. However, in contrast to our study, diminished 26 S proteolytic activity has been found to be accompanied by a loss of 26 S proteasomal structure following exposure to metal-catalyzed oxidation as a result of carbonylation involving one of the S6 ATPase regulatory subunits (58). Strong oxidation of the 26 S proteasome under non-physiologic conditions can occur by exposure to hydroxyl radical generated in metal catalyzed reactions; in the present study, exposure of the 26 S proteasome to GSH and H 2 O 2 was performed in the presence of metal chelator diethylenetriaminepentaacetic acid, eliminating the possibility of such hydroxyl radical-associated events.…”
Section: Discussioncontrasting
confidence: 99%
“…Our Although the present experiments, as well as findings from previous studies (58), demonstrate that H 2 O 2 can induce functionally relevant oxidative modifications of 26 S subunits that directly result in diminished proteasomal activity, it is possible that increased intracellular H 2 O 2 concentrations may also modulate proteasomal function through other mechanisms. For example, decreased expression of Rpn11, a 19 S RP subunit, was found to be associated with aging (59), a condition known be accompanied by increased ROS formation (60).…”
Section: Discussionsupporting
confidence: 65%
“…Oxidation and glutathionylation itself may affect proteasome activity (51,52). Previous studies have shown that proteasomes are prone to oxidation (53).…”
Section: Discussionmentioning
confidence: 99%
“…S-Nitrosylation could also inactivate these enzymes (Yao et al, 2004). Reactive oxygen species and reactive lipid peroxidation products, such as 4-hydroxynonenal, also impair the function of the proteasome (Conconi et al, 1998;Okada et al, 1999;Caballero et al, 2003;Ishii et al, 2005). Since the UPP plays critical roles in almost every aspect of cellular function, abnormal regulation or inactivation of this pathway has been implicated in many age-related diseases, such as Alzheimer's disease (Hope et al, 2003), Parkinson's disease (Dawson and Dawson, 2003), and cataract (Jahngen-Hodge et al, 1992;Shang et al, 1997;Shang et al, 2001;Dudek et al, 2005).…”
Section: Introductionmentioning
confidence: 99%